2013
DOI: 10.1521/jscp.2013.32.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Daily Ups and Downs in Women's Binge Eating Symptoms: The Role of Basic Psychological Needs, General Self-Control, and Emotional Eating

Abstract: the high prevalence rates of problematic eating behaviors, such as binge eating symptoms, have urged researchers to investigate why and when control over eating behaviors is lost. the current study employs a daily diary methodology to examine whether the daily satisfaction and frustration of the basic psychological needs for autonomy, competence, and relatedness, as conceptualized within Self-determination theory (deci & ryan, 2000), is associated with daily binge eating symptoms. in a sample of female adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 52 publications
(72 reference statements)
5
77
1
Order By: Relevance
“…Presumably, episodes of binge eating may elicit feelings of incompetence or may prompt feelings of guilt, which could result in low need fulfillment. Note that this particular finding deviates from the diary study by Verstuyf et al (2013), who reported that, on a day-to-day basis, binge eating covaried with need frustration, but not with need satisfaction. Before providing any interpretation, future research may want to replicate the current finding.…”
Section: Psychological Need Frustration and Binge Eating Symptomscontrasting
confidence: 99%
See 1 more Smart Citation
“…Presumably, episodes of binge eating may elicit feelings of incompetence or may prompt feelings of guilt, which could result in low need fulfillment. Note that this particular finding deviates from the diary study by Verstuyf et al (2013), who reported that, on a day-to-day basis, binge eating covaried with need frustration, but not with need satisfaction. Before providing any interpretation, future research may want to replicate the current finding.…”
Section: Psychological Need Frustration and Binge Eating Symptomscontrasting
confidence: 99%
“…Daily diary studies have shown that perfectionism (Boone, Soenens, Thanasis, et al, 2012), need frustration (Verstuyf et al, 2013), and binge eating (Sherry & Hall, 2009) fluctuate from day to day within individuals, and have shown that they influence each other during the course of one day. However, no study has examined the interrelations between these constructs simultaneously at the level of daily fluctuation.…”
Section: Limitations and Research Suggestionsmentioning
confidence: 99%
“…In a sample of female adolescents, they showed indeed that an investment in appearance-focused motives led to need frustrations, which in turn predicted increased bulimic symptoms. Along similar lines, a diary study in female adolescents (Verstuyf, Vansteenkiste, Soenens, Boone, & Mouratidis, 2013) indicated that daily variation in psychological need frustration covaried with ups and downs in bulimic symptoms, suggesting that binge eating serves to compensate for painful experience of need frustration.…”
Section: Autonomy Disturbances In Development and Psychopathology 419mentioning
confidence: 87%
“…For example, on days when basic psychological needs are frustrated, problems with eating regulation are more likely to occur (Verstuyf, Vansteenkiste, Soenens, Boone, & Mouratidis, 2013). In addition, psychological need satisfaction has been found to play a role in peoples' sexual experiences (Smith, 2007).…”
Section: Introductionmentioning
confidence: 99%